Employer internship recruiting on college campuses: 'the right pipeline for our funnel'. Issue 4 (19th May 2021) - Smith, Katie N.; Green, Demetrius K.
ABSTRACT: This case study examines the ways in which employers recruit undergraduate students on U.S. college campuses for internship opportunities. More students today are completing internships than ever before, and career services offices on college campuses are increasingly partnering with employers to promote these opportunities. For students, internship experiences build career knowledge and skills and can lead directly to professional opportunities. For employers, internship programmes aid the recruitment and training of future employees. Given the potential relationship between internships and post-graduate opportunities for students, understanding the ways in which employers recruit student interns has important implications for higher education today. To provide a multi-dimensional understanding of the recruitment of college students for internship positions, data were collected from nine employers and 16 career services staff members who interact with internship recruiting processes on college campuses in North Carolina. Six major themes emerged: identifying target institutions and environments, campus connection points, establishing a brand, creeping recruitment timelines, targeting early students, and converting interns to full-time employees.